Concomitant Polymorphism and Nucleation Control of DL‐Methionine Through Antisolvent Crystallization. Issue 4 (23rd February 2021) - Suresh, Manivel; Srinivasan, Karuppannan
Abstract: The concomitant polymorphism of the sulfur‐containing essential amino acid DL ‐methionine was revealed, and α ‐ and β ‐polymorphic forms were separated from aqueous solution through antisolvent crystallization with ethanol as antisolvent. The addition of different volume fractions of ethanol into the mother solution reduces the solubility of DL ‐methionine in double‐distilled water and in turn proportionately generates a range of supersaturation levels. This induces the nucleation of a stable β ‐polymorph at low supersaturation levels, a mixture of α ‐ and β ‐ polymorphs at intermediate supersaturation levels, and a metastable α ‐form at high supersaturation levels. Needle‐shaped α ‐polymorphs and platy‐shaped β ‐polymorphs were well distinguished through in‐situ optical microscopic analysis and their structural confirmation was done by X‐ray diffraction analysis. Abstract : Nucleation control and effective separation of concomitant type metastable α ‐ and stable β ‐polymorphs of DL ‐methionine from aqueous solution through crystallization in the presence of the antisolvent ethanol were carried out. The addition of this antisolvent reduces the solubility of DL ‐methionine in double‐distilled water and proportionately enhances the level of supersaturation.